Assessing engineering thinking in the context of biology among senior high school students in mainland China: development and validation of a two-tier assessment scale and the relationship between self-efficacy and practical performance - Ma, Huangdong; Liu, Wencheng; Liu, Bo; Lu, Yang; Li, Gaofeng (Frontiers in Education, 2025)
This study designed and validated the Engineering Thinking Assessment Scale (ETAS) to assess the engineering thinking of senior high school students in mainland China and to explore the correlation between their self-efficacy in different engineering thinking elements and their practical performance. The ETAS, comprising 28 items, was designed through four phases: defining dimensions, designing, pilot testing, and final assessment. Each item includes two tiers: the emotional tendency tier, measuring self-efficacy, and the practical performance tier, assessing actual application in engineering projects. A study with 510 students (485 valid responses) confirmed the scale's strong reliability and validity. While most students demonstrated above-average engineering thinking, higher self-efficacy did not consistently translate to better performance. Notably, 10 engineering thinking elements showed weak correlations (0.2 < |r| < 0.3) between self-efficacy and performance, indicating confidence without effective application. This study offers a detailed evaluation of engineering thinking abilities, highlighting gaps between perceived and actual competency in specific engineering elements.